(untitled) (Andamios, Revista de Investigación Social, 2013)
The measurement of the relative quality of electoral candidates could be biased by ideology. We properly justify considering a model of spatial competition with three parties for Mexico. We compare the results of the presidential elections with the expected ones from the ideological distribution of Mexicans. Through this comparison we provide a ranking of the valence or quality of the candidates for the presidential elections of 2006 and 2012.